Hybrid libraries: a discourse analysis of the Central Library at Liverpool - Silva, Rafaela Carolina da [UNESP]; Lima, Larissa de Mello [UNESP]; Kiyonaga Suenaga, Cynthia Maria [UNESP]; Martinez-Avila, Daniel [UNESP]; Ernesto Moraes, Joao Batista [UNESP] (Ibersid Network, 2017)
Hybrid libraries allow a greater interaction between the professional practice and the users of an information unit. In this sense, they are information links between traditional and digital libraries. Due to their greater flexibility in offering services and products, they must be studied using a rich methodology that can be adapted to the form and statements stemmed from those environments. Its social perspective provides the organizational structure with policies for the development of communities, also contributing to a good functioning of the institution. In that perspective, the research question of this paper refers to the potential of hybrid libraries for society. The discourse analysis based on Orlandi, that revises the works of Foucault and Pecheux in advertising, enables the analysis of the discourse of the Central Library at Liverpool in the United Kingdom. This institution, through the inclusion of another information unit such as the archive, reflects the ideal of a hybrid library to be applied in other information units. The analysis found that the adaptation of other information units such as archives to the hybrid library environment affects the ability of users to discover new information and investigate the information that the library is providing.
Keywords: Hybrid libraries; Archive of the Central Library at Liverpool; Discourse analysis; Advertisement discourse; United Kingdom